Management of COVID-19 patients, with emphasis on limited resource setting: is less optimum? - Samant, Prafulla; Ghodge, Siddhi; Sankhe, Ajay; Ali, Heena; Gawali, Vijaykumar; Bhadre, Manoj Kisanrao; Mhatre, Swati Suyog; Bhagat, Pradnya Anil; Pawar, Santosh Sudhakar; Madhavi, Rajendra; Patil, Sushil Shashikant (International Journal of Advances in Medicine, 2021)
Background: There is scarcity of essential medications, medical talent and health care facilities to treat covid-19, at remote places. This study explores various modalities in resource-limited settings for the management of COVID-19 patients. Methods: We retrospectively analysed data of 266 consecutive discharged and death Covid-19 patients from 26December 2020 to 29May 2021. All patients were admitted and received appropriate supportive care, regular clinical and laboratory monitoring. Results: Of total 266 patients the mean age of patients was 49.19 (SD 14.1) years and 185 (69.54%) of them were males. 99 (37%) cases were moderate, 83(31%)were severe cases remaining 84 (32%) were mild cases. 16 (6.01%) patients expired and remaining 250 patients were subsequently discharged. Median duration of stay in the hospital was 9 (37) days. Of total 266 admitted patients’ mortality rate was only 6.01%. Conclusions: We emphasize that even in healthcare facilities with limited resource, poor infrastructure and lack of ICU facilities, clinical observation-based managementt can help to reduce mortality considerably. Unique features of our study include; use of progesterone as an immunomodulator, use of dual antiviral agents, use of age-related lower limit of oxygen saturation.